2008
DOI: 10.1159/000165629
|View full text |Cite
|
Sign up to set email alerts
|

Patch Tests in Children with Suspected Allergic Contact Dermatitis: A Prospective Study and Review of the Literature

Abstract: Aims: The results of patch testing in children visiting our out-patient clinic with suspected allergic contact dermatitis (ACD) were prospectively investigated and compared with those reported in the literature. A review of the literature on patch testing and ACD in children is provided. Methods: Children were patch tested using the TRUE® test, supplemented with tixocortol-17-pivalate, budesonide and 3 commonly used emollients. Supplementary patch tests were undertaken on indication. Results: Seventy-nine chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
4
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 60 publications
8
48
4
2
Order By: Relevance
“…In studies conducted with children with AD, the frequency of thimerosal sensitization was reported as between 1.5% and 12.2% in the patch-tested population (10,17,30). In our study, the thimerosal sensitization rate was 5.2% (7/134).…”
Section: Discussionsupporting
confidence: 44%
“…In studies conducted with children with AD, the frequency of thimerosal sensitization was reported as between 1.5% and 12.2% in the patch-tested population (10,17,30). In our study, the thimerosal sensitization rate was 5.2% (7/134).…”
Section: Discussionsupporting
confidence: 44%
“…Sensitization to contact allergens begins in infancy and continues to be more common in toddlers and young children (Seidenari et al, 1992;Giordano-Labadie et al, 1999;Vozmediano & Hita, 2005;Militello et al, 2006;Clayton et al, 2006;Garg et al, 2009;De Waard-van der Spek & Oranje, 2009), the age of sensitization can occur very early. In study of Bruckner et al (Bruckner et al, 2000), 45% of patients with positive reactions were younger than 18 months.…”
Section: Prevalence Related To Agementioning
confidence: 99%
“…De Waard-van der Spek and Oranje (De Waard-van der Spek & Oranje, 2009) found 3 children patch tested positive to sorbitan sesquioleate (SSO), all clinically relevant. Two children used emollient contained SSO as emulsifier.…”
Section: Sorbitan Sesquioleatementioning
confidence: 99%
“…In der Epikutantestung (Inhaltsstoffe der topi schen ADTherapie) reagierten 6% der Kinder positiv. In einer deutlich kleine ren prospektiven Untersuchung aus den Niederlanden fand sich sogar bei 47% der Kinder mit einer AD (mittleres Al ter 10 Jahre) eine positive Epikutantestre aktion [10]. Anhand dieser beiden Stu dien ist exemplarisch gut ersichtlich, dass eine Vergleichbarkeit der Prävalenzdaten in Anbetracht unterschiedlich großer Pa tientenkollektive und verschiedener getes teter Testreihen erschwert ist.…”
Section: Introductionunclassified